Descriptive study of incidence of side effects of Pegylated interferon alpha therapy and their relation to age, gender, duration of treatment and type of hepatitis in 50 Iraqi patients. - AL-Khazraji, Khalid A. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Hepatitis C and B is common disease all over the world and their chronicity is a social and medical problem so medical treatment by alpha interferon can change the mortality and morbidity. Object: Identify the incidence of the side effects of pegylated interferon alpha in a sample of Iraqi patients with chronic hepatitis B&C and their relation to age, gender, duration of treatment and type of hepatitis comparing them with the literatures from other countries. Patients and methods:A descriptive case series study was conducted on 50 patients, 24 male and 26 female, with established diagnosis of hepatitis B(20 patients)and C(30 patients) who attend Baghdad Teaching hospital and Gastroenterology and Hepatology centre in Baghdad between the period of January 2009 and October 2010 with follow up over at least 3 months. A direct interview with detailed history and thorough clinical examination with some simple laboratory investigation were done to determine any of the documented side effects of alpha interferon therapy or discover new side effects not elicited in the studies done on other populations. Results: Flu-like illness is the most common side effect (84%), followed by fatigue, anorexia, local reaction and neuropsychiatric side effects while Neutropenia, lymphopenia and thyroiditis are rare. There is no significant difference in the incidence of side effects between age groups with the exception of constipation which occurs more in younger age group. Arthralgia, palpitation, eczema, itching and rash increase in incidence with prolonged duration of treatment. There is no significant difference in incidence of side effects between both genders apart from hypertension (more in female) and dizziness (more in male). There is no significant difference in incidence of side effects between patients with hepatitis B&C but anemia occurs more in patients with hepatitis C and tremor reported more in patients with hepatitis B. Conclusion: Almost all patients on treatment with interferon-based regimen will experience adverse events that can threaten good adherence. Flu-like illness is the most common side effect (84%), followed by fatigue, anorexia, local reaction and neuropsychiatric side effects (depression, nervousness, insomnia). The higher incidence of anemia in patients with hepatitis C is mostly due to concomitant ribavirin therapy. Age, gender, type of hepatitis and duration of treatment can affect the incidence of interferon therapy.